2019
DOI: 10.1029/2018jf004921
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference of Subglacial Channel Structures From Water Pressure and Tracer‐Transit Time Data: A Numerical Study Based on a 2‐D Geostatistical Modeling Approach

Abstract: Characterizing subglacial water flow is critical for understanding basal sliding and processes occurring under glaciers and ice sheets. Development of subglacial numerical models and acquisition of water pressure and tracer data have provided valuable insights into subglacial systems and their evolution. Despite these advances, numerical models, data conditioning, and uncertainty quantification are difficult, principally due to high number of unknown parameters and expensive forward computations. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Similar geostatistical methods are often used for simulating uncertainties and/or unknown heterogeneity on surfaces or materials, flow routing algorithms, etc. [57,58]. It is noteworthy that no variability is incorporated if the noise term is too small.…”
Section: Stochastic Least-cost Pathsmentioning
confidence: 99%
“…Similar geostatistical methods are often used for simulating uncertainties and/or unknown heterogeneity on surfaces or materials, flow routing algorithms, etc. [57,58]. It is noteworthy that no variability is incorporated if the noise term is too small.…”
Section: Stochastic Least-cost Pathsmentioning
confidence: 99%
“…Brinkerhoff and others (2016) used a Bayesian approach to condition a 0-D model of glacier hydrology and sliding on surface velocity and terminus flux observations to infer probability distributions over unknown ice dynamics and hydrologic model parameter. Although not coupled to an ice dynamics model, Irarrazaval and others (2019) present a Bayesian inference over the lattice model of Werder and others (2013), constraining the position and development of subglacial channels from observations of water pressure and tracer transit times. Aschwanden and others (2016) demonstrated that outlet glacier flow can be captured using a simple local model of subglacial hydrology, but further improvements are required in the transitional zone with speeds of 20–100 m a.…”
Section: Introductionmentioning
confidence: 99%